Prevention of Brachial Plexus Injury—12 Years of Shoulder Dystocia Training: An Interrupted Time-Series Study. Issue 5 (May 2016) - Crofts, J. F.; Lenguerrand, E.; Bentham, G. L.; Tawfik, S.; Claireaux, H. A.; Odd, D.; Fox, R.; Draycott, T. J.
Abstract : Abstracted from BJOG 2016;123:111–118 Shoulder dystocia remains a largely unpredictable event in which the fetal shoulders are trapped above the inlet to the maternal pelvis, hindering delivery of the baby and which can result in serious long-term morbidity for both mother and baby. In particular during traction on the fetal head when the shoulders are trapped, there is stretch and sometimes disruption of the nerves in the brachial plexus responsible for motor activity of the arm.